Evaluation of The Role Syech Tambuh Foundation Community Work Training Center In Improving The Quality of Human Resources - Ahsri Oktafiani; Achmad Romadin; Didik Nurhadi (Journal of Vocational Education Studies, 2022)
The Community Work Training Center has a mission to produce unskilled Human Resources to become skilled in several areas of expertise and have entrepreneurial skills. The aim of this research is to evaluate the role of Community Work Training Center of Syech Tambuh Foundation in improving the quality of Human Resources in in Islamic boarding schools and the surrounding environment. This research approach was descriptive qualitative. The source of data was obtained from observation, interviews, and documentation. The findings showed that the role of the Syech Tambuh Foundation Community Work Training Center is quite good. This foundation has used the curriculum standardized by the Ministry of Manpower. Syech Tambuh Foundation Community Work Training Center has collaborated with BRI, Bank Mandiri, Sampoerna Foundation and ITS. Generally, its graduates have become entrepreneurs and worked in several local and national industries. The conclusion of this research is that the role of Syech Foundation Community Work Training Center has grown quite well in providing training. Optimization of cooperation programs needs to be carried out to support the improvement of the quality of training in providing experience for the training participants